Monitoring the exposure and emissions of antibiotic resistance: Co-occurrence of antibiotics and resistance genes in wastewater treatment plants. (4th July 2022) - Steenbeek, Ruud; Timmers, Peer H. A.; van der Linde, Danielle; Hup, Kay; Hornstra, Luc; Been, Frederic
Abstract: The COVID-19 pandemic has brought new momentum to 'wastewater-based epidemiology' (WBE). This approach can be applied to monitor the levels of antibiotic-resistant genes (ARGs), which in terms are used to make inferences about the burden of antimicrobial resistance (AMR) in human settlements. However, there is still little information about temporal variability in ARG levels measured in wastewater streams and how these influence the inferences made about the occurrence of AMR in communities. The goal of this study was hence to gain insights into the variability in ARG levels measured in the influent and effluent of two wastewater treatment plants in The Netherlands and link these to levels of antibiotic residues measured in the same samples. Eleven antibiotics were detected, together with all selected ARGs, except for VanB . Among the measured antibiotics, significant positive correlations ( p > 0.70) with the corresponding resistance genes and some non-corresponding ARGs were found. Mass loads varied up to a factor of 35 between days and in concomitance with rainfall. Adequate sampling schemes need to be designed to ensure that conclusions are drawn from valid and representative data. Additionally, we advocate for the use of mass loads to interpret levels of AMR measured in wastewater. HIGHLIGHTS: Monitoring of antibiotics and antibiotic-resistant genes (ARGs) by wastewater-based epidemiology (WBE). Able to detect 11 antibiotics and 13 corresponding ARGs. Correlations found between antibiotics and ARGs in effluent. Important variability in ARG mass loads observed between sampling days. WBE needs to be implemented to design adequate sampling schemes to avoid misinterpreting the burden of antibiotic resistance. Graphical Abstract